Pelaksanaan Layanan Referensi Di Perpustakaan Iain Kediri - Achmad Muslih (LP2M Institut Agama Islam Negeri (IAIN) Kediri, 2021)
The service of reference aims to assist library users in finding information, by answering questions using reference collections, and providing guidance on finding and how to use reference collections. This study wants to answer two questions; firstly theimplementation of reference services at the IAIN Kediri library, secondly, the obstacles that occur in the implementation of reference services, and how to resolve these obstacles. This research is a qualitative research, which is trying to describe the implementation of reference services at the IAIN Kediri Library. The data source of this research is field data obtained from observations and documentation and interviews with reference librarians. The results of this study indicate that the reference services at the IAIN Kediri library are search services, reference collection utilization services and collection utilization training services. In the implementation of reference services, there are a number of obstacles as follows: first, the competence of human resources for librarians, second, the lack of complete collections and third, the lack of promotion of reference services. To overcome this problem, it can be done through tiered education for reference librarians, collaborating with various parties and conducting regular evaluations to build a quality culture (corporate culture) in the library.